MOTIVASI BGMC (BUILDING GREEN MODERN COSTRUCTION) CORPORATE SDN BHD MALAYSIA MELAKUKAN INVESTASI DI KAWASAN INDUSTRY TANJUNG BUTON SIAK RIAU - Novita Sari; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The research describe why BGMC (Building Green Modern Construction) Corporate SdnBhdMalaysia invests in the TanjungButonSiak Riau industrial estates. The TanjungButon Industrial Siak Riau Industrial estates is one of the industrial areas included in the National Strategic Project, in addition to the industrial estate TanjungButonSiak Riau is located close to the Malacca Strait which is one of the international trade routes. BGMC (Building Green Modern Construction) Corporate SdnBhd Malaysia is a company from Malaysia which engaged is construction and services, this research focuses on 2018 until now and uses interview research methods and also literature studies.TanjungButon industrial Estate to date is still in the process of being developed into an industrial area that can compete with other industrial areas. This study found that BGMC was interested in investing in the TanjungButonSiak Riau industrial estate because of the location TanjungButonIndustrial area is very strategic close to the Malacca Strait and Abnundant natural Resourch. The form of BGMC invesment in the TanjungButonSiak Industrial area is the development of existing developments in the industrial area towards an industrial area that is modern and alsoenviromentally friendly. Keywords: KITB, BGMC,CPO, foreign Invesment